Conflict in Syria compounds vulnerability of Palestine refugees - White, G (Refugee Studies Centre, University of Oxford, 2013)
Palestine refugees in Syria find themselves once more engulfed in a cycle of conflict and displacement that exacerbates their underlying vulnerability and highlights the ongoing need for durable solutions